Antitumour activity of an inhibitor of miR-34a in liver cancer with β-catenin-mutations. Issue 6 (19th March 2015) - Gougelet, Angélique; Sartor, Chiara; Bachelot, Laura; Godard, Cécile; Marchiol, Carmen; Renault, Gilles; Tores, Frédéric; Nitschke, Patrick; Cavard, Catherine; Terris, Benoit; Perret, Christine; Colnot, Sabine
Abstract : Objective: Hepatocellular carcinoma (HCC) is the most prevalent primary tumour of the liver. About a third of these tumours presents activating mutations of the β-catenin gene. The molecular pathogenesis of HCC has been elucidated, but mortality remains high, and new therapeutic approaches, including treatments based on microRNAs, are required. We aimed to identify candidate microRNAs, regulated by β-catenin, potentially involved in liver tumorigenesis. Design: We used a mouse model, in which β-catenin signalling was overactivated exclusively in the liver by the tamoxifen-inducible and Cre-Lox-mediated inactivation of the Apc gene . This model develops tumours with properties similar to human HCC. Results: We found that miR-34a was regulated by β-catenin, and significantly induced by the overactivation of β-catenin signalling in mouse tumours and in patients with HCC. An inhibitor of miR-34a (locked nucleic acid, LNA-34a) exerted antiproliferative activity in primary cultures of hepatocyte. This inhibition of proliferation was associated with a decrease in cyclin D1 levels, orchestrated principally by HNF-4α, a target of miR-34a considered to act as a tumour suppressor in the liver. In vivo, LNA-34a approximately halved progression rates for tumours displaying β-catenin activation together with an activation of caspases 2 and 3. Conclusions: This work demonstrates the key oncogenic role of miR-34a in liver tumours with β-catenin gene mutations. We suggest that patients diagnosed with HCC with β-catenin mutations could be treated with an inhibitor of miR-34a. The potential value of this strategy lies in the modulation of the tumour suppressor HNF-4α, which targets cyclin D1, and the induction of a proapoptotic programme.